How does access to education influence political candidacy? Lessons from school openings in Sweden - Karl-Oskar Lindgren; Sven Oskarsson; Mikael Persson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
How does availability of education affect who becomes a political representative? Theorists have pointed out access to education as a key to a well-functioning democracy, but few empirical studies have examined how changes in the access to education influence the chances of becoming a politician. In this paper we analyze the effects of a substantial series of school openings during the early 20th century in Sweden which provided adolescents with better access to secondary education. We use unique administrative data pertaining to the entire Swedish population born between 1916 and 1945. According to our empirical results the opening of a new lower secondary school in a municipality increased the baseline probability of running for political office by more than 10 percent and the probability of holding office by more than 20 percent.
Keywords: H7; I2; 330; education; political representation; elections